2014
DOI: 10.2319/122613-946.1
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of brackets and tubes:A twelve-month assessment

Abstract: Objective: To compare the clinical performance of brackets bonded to anterior and posterior teeth, including second molars. Materials and Methods: One operator, using the straight-wire technique, bonded metallic brackets to the teeth of 127 consecutive patients. All patients were observed for 12 months during their regular orthodontic appointments. Bracket failures were recorded and summarized for statistical analysis. The Cox proportional hazards regression analysis was performed to evaluate bracket failure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 26 publications
5
23
3
2
Order By: Relevance
“…13 In an investigation using a sample size of 128 patients, no significant difference between bracket failure rates of incisors vs premolars was found. 8 In our study, we found a significantly higher failure rate for orthodontic appliances in the mandible compared with the maxilla. This finding has been mentioned in other studies, but in this study, the difference was not statistically different.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…13 In an investigation using a sample size of 128 patients, no significant difference between bracket failure rates of incisors vs premolars was found. 8 In our study, we found a significantly higher failure rate for orthodontic appliances in the mandible compared with the maxilla. This finding has been mentioned in other studies, but in this study, the difference was not statistically different.…”
Section: Discussionsupporting
confidence: 51%
“…2,3,8 For molar tubes, bonding failures between 10.6% and 13.8% were reported. 2,8 It is difficult to compare outcomes of our study with previously published studies as their materials and methods were different. However, failure rates found in this study are within the range of previously published failure rates.…”
Section: Discussionmentioning
confidence: 99%
“…Bonding on molars have been associated with frequent attachment failures and white spot lesions. 2,3,[9][10][11] Banding is associated with gingival enlargement and increased pocket depth. 4,8,[12][13][14][15] The adolescents have more gingival enlargement than the adults.…”
Section: Discussionmentioning
confidence: 99%
“…However there is a high risk of bonding failure and white spot lesion associated with molar tubes. [2][3][4] In a very recent Cochrane review on banding versus bonding, it has been found that there is statistically significant difference on the rate of banding versus bonding failures. According to that review there is 57 % risk of attachment failure in case of bonded tubes whereas the risk is only 25 % in case Dr Dashrath Kafle, 1 Dr Aradhana Agarwal, 2 Dr Sita Shrestha, 3 Dr Biplov Adhikari of banded attachments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation